(untitled) (Scientific journal of the Fergana State University, 2024)
This article is devoted to the study and analysis of various aspects of the integration of chemical tasks into the chemistry teaching process. Chemistry problem integration is an important component of the educational process because it promotes a deep understanding of chemical concepts, the development of critical thinking, and the application of acquired knowledge in practice. The work includes an analysis of methods and strategies for integrating chemical tasks into the educational process, including the use of interdisciplinary connections with other natural sciences, such as biology, physics and mathematics. Practical aspects of introducing integrated tasks into the educational process are also considered, including the development of educational materials, teaching methods and student assessment. The purpose of the study is to increase the effectiveness of teaching chemistry and develop in students the competencies necessary for successful work in the field of chemistry and related sciences.